PENERAPAN MODEL PEMBELAJARAN TGT (TEAM GAME TOURNAMENT) MELALUI MEDIA WORDWALL UNTUK KETERAMPILAN MEMBACA PEMAHAMAN KELAS XI SMAN 1 MENGANTI - Afiyah, Naila Nur; Wahyuningsih, Fahmi (LATERNE, 2023)
Comprehension reading skills have become an essential skill that students must master in learning the German language. The subject of German Language at SMAN 1 Menganti is categorized as a specialization subject; however, many students face difficulties in their comprehension reading abilities. To address this issue, it’s important to consider various teaching methods and more interactive reading materials. The Team Game Tournament (TGT) learning model encourages collaboration among students, while Wordwall is used as the tournament medium. This research applies a quantitative research method with a pre-experimental one-group pretest-posttest design. The population in this study consists of 30 students from class XI-7 at SMAN 1 Menganti. Based on the Test of Normality Wilcoxon test output, the Asymp. Sig. (2-tailed) value obtained is 0.000. Since 0.000 < 0.05, it can be concluded that the alternative hypothesis (Ha) is accepted. This means that there is a difference in learning outcomes before and after using the TGT model through Wordwall . Therefore, it can be inferred that there is an influence of using the TGT learning method through Wordwall on the reading comprehension learning outcomes of students in class XI-7 at SMAN 1 Menganti.